An Interdisciplinary Approach for Rehabilitation of a Patient with Amelogenesis Imperfecta: A Case Report - Bista, Soni; Adhikari, Khushbu; Baniya, Bikash Kumar; Subedi, Suraksha; Pandey, Amrita; Bhadel, Reecha (Journal of Nepalese Society of Periodontology and Oral Implantology, 2022)
An interdisciplinary approach can be used to treat the uncommon hereditary defect known as amelogenesis imperfecta, which is characterised by insufficient crown length, hypersensitivity, dental caries, and decreased vertical dimension. The present case report describes a successfully managed case of amelogenesis imperfecta with full mouth rehabilitation using implant supported prosthesis. This interdisciplinary approach helped to restore the function and aesthetic of an adult patient, which was followed up for six years without any complications.